Petrologic and geochemical exploration of the plumbing systems under submarine volcanoes Edifice C, Three Sisters and Orca (Bransfield Strait, Antarctica) - Antonio Polo-Sánchez; Antonio M. Álvarez-Valero; Marcos García-Arias; Adelina Geyer; Helena Albert; Antonio Caracausi; Jérémie Malecki; Esteban S. Bertea; Maurizio Petrelli; Meritxell Aulinas; José Antonio Lozano-Rodríguez (Journal of Volcanology and Geothermal Research, 2026)

Volatiles in the mantle below Northern Antarctica: Insights from Deception Island volcano - Antonio Caracausi; Antonio Polo-Sánchez; Antonio M. Álvarez-Valero; Jabrane Labidi; Edward D. Young; Hirochika Sumino; Conxita Ávila; Dario Buttitta; Adelina Geyer; Paolo Randazzo (Gondwana Research, 2026)

Preharvest treatment with brassinosteroids as an effective tool to improve commercial postharvest quality of blood orange cv. ‘Sanguinelli’ - Fernando Garrido-Auñón; Jenifer Puente-Moreno; María E. García-Pastor; Juan M. Valverde; Vicente Agulló; María Serrano; Daniel Valero (Food Chemistry, 2026)

Correction to: Assessment of the macroalgal genetic resources maintained in European germplasm banks - Laurie Carol Hofmann; Inka Bartsch; Hendrik Pehlke; Cicero Alves-Lima; Luís M. Barreto; Ricardo Bermejo; Susana Coelho; Olivier De Clerck; Bente Edvardsen; Svenja Heesch; Vladyslava Hostyeva; Lucie Jaugeon; et al. (Journal of Applied Phycology, 2026)

Assessment of the macroalgal genetic resources maintained in European germplasm banks - Laurie Carol Hofmann; Inka Bartsch; Hendrik Pehlke; Cicero Alves-Lima; Luís M. Barreto; Ricardo Bermejo; Susana Coelho; Olivier De Clerck; Bente Edvardsen; Svenja Heesch; Vladyslava Hostyeva; Lucie Jaugeon; et al. (Journal of Applied Phycology, 2026)
Germplasm banks are important for preserving genetic diversity, yet the availability and long-term maintenance of macroalgal strains in germplasm banks is currently limited in European collections. To support future food security, restoration efforts, and biotechnological innovation, a strategy was recently developed for the long-term preservation of macroalgal genetic diversity. A foundational step in this effort is to assess the existing biodiversity, biogeographical distribution, and commercial relevance of seaweed cultures maintained in European collections. Using a universal data-collection template distributed widely across European seaweed networks, we compiled and analysed information on these seaweed cultures. As of November 2025, the resulting SeaStrains Database of European Seaweed Collections contains 2541 cultures representing 426 species, accounting for only 4% of global and 15% of European macroalgal diversity. The dataset reveals strong taxonomic bias: 74% are brown seaweeds (Ochrophyta), dominated by Laminaria , Saccharina , and Ectocarpus . Saccharina latissima is the most preserved species due to its scientific and commercial importance. Red and green algae are markedly underrepresented (11% and 14%, respectively), likely reflecting cultivation challenges and life-cycle knowledge gaps. Biogeographically, most cultures originate from cold- to warm-temperate zones, with limited representation of the South Atlantic, Indian Ocean, polar and remote regions. Over 60% of cultures are maintained at two institutions: the Culture Collection of Algae and Protozoa (Scotland) and the Alfred Wegener Institute (Germany). This work provides transparent, accessible information on Europe’s macroalgal germplasm resources and represents a crucial step toward a more robust and sustainable European seaweed sector aligned with UN SDG Target 2.5.

E-selectin and transferrin receptor functionalized synthetic miRNA nanoshuttles with therapeutic potential in stroke - Valérie Petegnief; Maria Kannavou; Valeria Peli; Carles Justicia; Foteini Gkartziou; Alicia Aliena-Valero; Leire Pedrosa; Juan B. Salom; Dorian Tace; Anna M. Planas; Sophia G. Antimisiaris; Lorenza Lazzari (Drug Delivery and Translational Research, 2026)
Current acute ischemic stroke treatment is limited to reperfusion therapies within the first hours after the onset, underscoring the urgent need for novel therapeutic strategies to mitigate the progression of the brain lesion. Here, we describe the development of bio-inspired synthetic nanoshuttles—lipid nanoparticles (LNPs)—designed to deliver miRNAs and target post-stroke inflammation, a key contributor to secondary brain damage. miRNAs isolated from human induced pluripotent stem cells (hiPSCs) were encapsulated into LNPs prepared by a microfluidic technique. We produced small sized, uniform nanoparticles with high miRNA encapsulation efficiency. LNPs were functionalized with anti-transferrin receptor (TfR) and anti-E-selectin antibodies to target the inflamed cerebral vasculature. We assayed LNPs’ effect in a model of vascular inflammation in vitro and in vivo following brain ischemia/reperfusion in mice. In cultured human brain endothelial cells, empty LNPs, dual-targeted empty LNPs, and dual-targeted LNP encapsulating miRNAs (DT-LNP) reduced lipopolysaccharide-induced interleukin-6 production, indicating a modulatory effect of the lipid carrier under our experimental conditions. Mice received, via i.v., either empty LNPs (control) or two different doses of DT-LNPs at reperfusion following brain ischemia. The low dose of DT-LNPs reduced infarct volume and tended to improve the neurological deficit, and to downregulate the expression of IL-1β and E-selectin mRNAs, whereas the high dose did not. Altogether, these findings provide proof-of-concept that TfR-E-selectin-targeted LNPs encapsulating hiPSC-derived miRNAs represent a promising therapeutic approach for stroke.

Carboxyl-stabilized Mn redox cycling promotes a metastable kutnahorite-to-dolomite pathway - Daniel A. Petrash; Astolfo Valero; Or M. Bialik; Yihang Fang; Maartje Hamers; Travis B. Meador; Tomaso R.R. Bontognali; Michael Ernst Böttcher; Oliver Plümper (Geochimica et Cosmochimica Acta, 2026)

From Floods to Social Risks: Human-Centered Design for Safer Water Infrastructure - Brian M. Crookston; Daniel Valero (Water Resources Management, 2026)
Critical water infrastructure is designed to satisfy performance criteria and also withstand natural disasters such as extreme flood scenarios. Safety in this regard has improved drastically over the last century, yet hundreds of casualties occur each year at hydraulic structures from public interactions that include all types of routine social behaviors and recreational activities. For example, in the UK and US such drownings in one year have resulted in as many casualties as deaths due to dam failures in the last 200 years. Herein we explore UK and US official and crowdsourced data to expose a risk perception gap and a neglected class of infrastructure risk. At hydraulic structures, fatal activities across all human ages ranged from accidental to intentional interactions. Examples include walking along a scenic canal, visiting a park, or more intrusive behaviors such as fishing from a dam, canoeing, or sliding down a spillway. Some new activities may be inspired by social media. Contrary to common expectations, the routine interactions with hidden risks are weighty contributors to fatalities and data indicates that alcohol did not play a significant role in these accidents (< 13.5%, UK). Furthermore, only 15% of drownings occurred during swimming activities (UK). Also, public safety measures were generally found to be non-existent or inadequate (US), despite repeated injuries or fatalities at certain structures. Many of these public safety hazards would be readily solved at the design stage, but retrofits that consider local social behaviors can be viable for both newer and legacy infrastructure. Although some risk reduction efforts, including awareness campaigns, are underway for US low-head dams, most other hazards remain invisible, —with walking/running by waterways amounting to 37% of these casualties (UK)—; which contrasts with the complete lack of risk perception by the general population. For these water risks –concealed in plain sight –, several generally applicable solution strategies are proposed herein, hierarchical to their effectiveness and involving interdisciplinary engineering, operation, and governance.

Effects of two advanced footwear technology shoes on durability in trained male runners - A. Alda-Blanco; S. Rodríguez-Barbero; F. Valero; J. J. Salinero; V. Rodrigo-Carranza; J. M. González-Ravé; F. González-Mohíno (German Journal of Exercise and Sport Research, 2026)

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Alteration minerals and their formation environments in intrusion-related hydrothermal systems at Mt. Ruapehu (New Zealand) – New insights from mass balance, thermodynamic modelling and stable isotopes - Antonio M. Álvarez-Valero; Gabor Kereszturi; Rachelle Sánchez; David Benavente; Cristina Pérez-Coca; Mercedes Suárez; Bruce Christenson; Takumi Imura; Masao Ban (Journal of Volcanology and Geothermal Research, 2026)

Timescales and processes of hydrothermal alteration at Te Maari Tongariro, New Zealand: Insights utilizing petrographic and mass balance techniques - Rachelle Sanchez; Gabor Kereszturi; Antonio M. Álvarez-Valero; Mercedes Suárez; Geoff Kilgour; Georg Zellmer (Journal of Volcanology and Geothermal Research, 2026)

Hyperspectral imaging, mineralogy, and degassing: Exploring the volcanic hydrothermal system of Red Crater, Tongariro, Aotearoa New Zealand - Daniel Sturgess; Gabor Kereszturi; Agnes Mazot; Rachelle Sanchez; Antonio M. Álvarez-Valero; Vladyslav Zakharovskyi (Journal of Volcanology and Geothermal Research, 2026)

Ocular morphology and corneal histology in four avian species with different ecological patterns - R. Cobo; A. Navarro-Sempere; A. García-Martínez; E. Valero-Picó; Y. Segovia; M. García (Zoomorphology, 2026)
Vision plays a central role in the ecological success of birds, and morphological specialisations of the eye often reflect habitat use and behavioural strategies. As the principal refractive surface of the eye, the cornea is a key structure for visual performance, and its architecture may reflect ecological specialisation. In this study, we describe ocular morphology and corneal histology in four bird species with contrasting ecological profiles: the Eurasian sparrowhawk ( Accipiter nisus ), the booted eagle ( Hieraaetus pennatus ), the little bittern ( Ixobrychus minutus ), and the stone-curlew ( Burhinus oedicnemus ). Using light and transmission electron microscopy, we analysed morphometric parameters, tissue thickness, and cellular densities in both central and peripheral corneal regions. Interspecific differences were recorded in total corneal thickness, in the thickness of individual layers (epithelium, stroma, Bowman’s and Descemet’s membranes, and endothelium), and in keratocyte, epithelial, and endothelial cell densities. Accipiter nisus and Hieraaetus pennatus , two diurnal predators from open habitats, exhibited thicker corneas with greater stromal compactness and higher endothelial cell density. Ixobrychus minutus , a crepuscular species from dense wetlands, had a proportionally large cornea relative to eye size but reduced thickness, characterised by high epithelial cell density and frequent intracellular vacuolisation, possibly related to osmotic stress. Burhinus oedicnemus , adapted to arid and exposed habitats, presented a thickened Descemet’s membrane and more complex endothelial interdigitations. These descriptive findings document interspecific variation in ocular and corneal organisation among species occupying different ecological niches and establish a morphological reference for future comparative and functional studies.

Ascent rates of mantle xenoliths in low-viscosity magmas in eruptive phases: new insights from a quiescent volcano - Mathieu Berbineau; Hélène Balcone-Boissard; Céline Baudouin; Antonio M. Álvarez‑Valero; Antonio Caracausi; Gabriele Carnevale; Etienne Deloule; Michele Paternoster; Silvio G. Rotolo (Bulletin of Volcanology, 2026)
This study provides new insights into magma ascent based on mantle xenoliths erupted during the last explosive volcanic activity of Mt. Vulture volcano (southern Italy), combining H diffusion chronometry with fluid-mechanical models. Olivine crystals within lherzolite, wehrlite and dunite xenoliths are Mg-rich (Fo 88-90 ), with NiO contents up to 0.30 wt%. They show hydrogen loss profiles between 0.5 and 2.5 ppm, and the resulting xenolith ascent rates are up to 5 m s −1 . The fluid mechanical model also generates high magma ascent rates, with values up to three times faster (17 m s −1 ) than those computed with the H diffusion chronometry. Lag times between the ascent rates of the low-viscosity magma that transported the mantle xenoliths and the xenoliths themselves during the last eruption of Mt. Vulture (140 ka) are constrained to a few tens of minutes. To make the fluid mechanical and the H diffusion chronometry models compatible, a low density contrast between the ascending magma and the surrounding crust (Δϱ = 20–40 kg m −3 ) and a conduit diameter of 2–5 m are required. Our study highlights the importance of using independent models based on multiple parameters to constrain magma ascent rates. This could provide new means for reconstructing the volcanic activity of currently quiescent volcanoes, as carried out here for Mt. Vulture.

First multidisciplinary evidence of hydrothermal activity at Enmedio deep submarine volcano (Canary Islands) - Alba González-Vega; Juan Tomás Vázquez; José Antonio Lozano Rodríguez; Olga Sánchez-Guillamón; Desirée Palomino; Adelina Geyer; Rafael Bartolomé; Antonio M. Álvarez-Valero; Jesús M. Arrieta; Antonio Villaseñor; Juan Pablo Martín-Díaz; Carmen Presas-Navarro; et al. (Bulletin of Volcanology, 2026)
The deep submarine volcano Enmedio is located between Tenerife and Gran Canaria, the two most populated islands of the Canary archipelago. This study integrates multidisciplinary data gathered from 2015 to 2024, enabling a comprehensive analysis of the geomorphological, petrological, geochemical, and oceanographic features of this volcano. The combined findings from these disciplines confirm hydrothermal activity at the submarine volcano. The main volcanic cone is characterized by a fracture zone, which crosses it from NNW to SSE and passes over the summit, and a half-moon-shaped depression in the south-western flank, likely caused by a collapse event. In the surrounding area, at least 20 smaller volcanic reliefs have been identified, five of which present crater-like depressions. Backscatter data and seismic profiles suggest significant rock alteration at the fracture zone of Enmedio volcano. This alteration is corroborated by rock samples exhibiting surface modifications characterized by Fe-oxyhydroxide deposits, alongside microscopic filamentous textures typical of biogenic Fe-rich formations. These features suggest a strong association with hydrothermal environments. Additionally, geochemical analyses point to magmatic differentiation processes. The physical, chemical, and biological oceanographic parameters in the seawater show temperature anomalies, water column instabilities, enhanced turbidity, enrichment in inorganic nutrient concentrations, and an overall increase in prokaryotic abundance. These anomalies were found linked to some relevant geomorphological features, such as the summit fracture zone, the half-moon depression, and the two closest smaller volcanic cones. This integrated perspective highlights Enmedio as a focal point of hydrothermal and volcanic activity, shedding light on the dynamic relationship between geological and oceanographic processes in the Canary archipelago.

Palatability changes during attenuation of flavor neophobia assessed with licking microstructure and taste reactivity - S. Menchén-Márquez; M. Valero; P. Gasalla; F. Gámiz; M. Gallo; D.M. Dwyer (Appetite, 2026)

Mild valorisation process of polycotton waste using a recyclable ionic liquid for lactic acid production, combined with polyester recovery - H. Poy; M. Capilla; E. Lladosa; B. Taroncher; P. San-Valero; S. Loras; C. Silvestre; P. Ferrero; J. Álvarez-Hornos (Journal of Environmental Chemical Engineering, 2025)

Petrophysical properties of hydrothermally-altered pyroclastic deposits from Deception Island (Bransfield Strait, Antarctica) - Michael J. Heap; Adelina Geyer; Jasmine Dibben; James Hickey; Guillem Gisbert; Oriol Vilanova-Pagès; Jordi Ibañez-Insa; Antonio Polo-Sánchez; Santiago Giralt; Maëlys Moulin; Antonio M. Álvarez-Valero (Journal of Volcanology and Geothermal Research, 2025)

Canine eosinophilic pulmonary granulomatosis: Clinical-pathological diagnosis and physiopathology theories - L.X. Bravo-Coello; E. Carrillo-Castillo; A. Cervantes-Arias; M. Juárez-Ramírez; G. Valero-Elizondo (Journal of Comparative Pathology, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Characterization and potential causes of a whiting event in the Mar Menor coastal lagoon (Mediterranean, SE Spain) - Marijn Oosterbaan; Francisco Gómez-Jakobsen; Gonzalo G. Barberá; Jesús M. Mercado; Isabel Ferrera; Lidia Yebra; Blas Valero-Garcés; Antonio Delgado-Huertas; Marta Álvarez; Lázaro Marín-Guirao; Pedro Martínez Martínez; Victor Orenes-Salazar; et al. (Science of The Total Environment, 2025)

Co-benefits of residential retrofits: A review of quantification and monetization approaches - L. Ruiz-Valero; N. Makaremi; S. Haines; M. Touchie (Building and Environment, 2025)

Towards the establishment of a green and sustainable analytical methodology for hyperspectral imaging-based authentication of wholemeal bread - Miriam Medina-García; Esteban A. Roca-Nasser; Miguel A. Martínez-Domingo; Eva M Valero; Alejandra Arroyo-Cerezo; Luis Cuadros-Rodríguez; Ana M. Jiménez-Carvelo (Food Control, 2024)

Urinary concentrations of non-essential and essential elements during weaning in infants from the NELA cohort in Spain - Leyre Notario-Barandiaran; Eva Morales; Jesús Vioque; Carmen Martinez-Gracia; Marina Santaella-Pascual; Clara Suarez-Martinez; Luis Garcia-Marcos; Margaret R. Karagas; Antonio J. Signes-Pastor; M.E. Candel-Torralba; L. Garcia-Marcos (Pi); M.J. Gimenez-Banon; et al. (Environmental Research, 2024)

Transforming the food system: Are farmers ready to take phosphorus stewardship action? - Julia Martin-Ortega; Lukas J. Wolf; Emmanouil Tyllianakis; Aine Anderson; Miller Alonso Camargo-Valero; Dana Cordell; Donnacha G. Doody; Kirsty J. Ross; Brent Jacobs; Shane A. Rothwell; Shervin Shahvi; Erin Sherry; et al. (Environmental Science & Policy, 2024)

Prompt gamma facility for BNCT at RA3 reactor: Neutron beam adequation stage by simulation-guided design - M. Valero; L. Rogulich; S.I. Thorp; M.E. Miller; M. Sztejnberg (Annals of Nuclear Energy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sulfur isotopic variations in the products of the 1895 CE eruption at Zao volcano (NE Japan): Implications for connecting eruption source and syn-eruptive magmatic-hydrothermal processes - Takumi Imura; Tsukasa Ohba; Ryohei Takahashi; Pearlyn Manalo; Hinako Sato; Masao Ban; Aoi Hirata; Antonio M. Álvarez-Valero (Journal of Volcanology and Geothermal Research, 2024)

Commercial wine yeast nitrogen requirement influences the production of secondary metabolites (aroma, hydroxytyrosol, melatonin and other bioactives) during alcoholic fermentation - Marina Gonzalez-Ramirez; Julia Kazakova; Pedro Garcia-Serrano; Cristina Ubeda; Eva Valero; Ana B. Cerezo; Ana M. Troncoso; M. Carmen Garcia-Parrilla (International Journal of Food Microbiology, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Thirteen new species of Urucumania (Phasmatodea: Pseudophasmatidae) stick insects from Brazil and Bolivia - Victor M. Ghirotto; Edgar B. Crispino; Phillip W. Engelking; Pedro Alvaro Barbosa Aguiar Neves; Pablo Valero; Thiago Ferreira Soares; Thiago Silva-Soares; Thiago José De Souza Alves; Pedro Sisnando; Raphael A. Heleodoro; Oskar Conle; Frank Hennemann; et al. (Biologia, 2024)

Surface-layer turbulence associated with a fast spreading grass fire - Shiyuan Zhong; Melissa Gonzalez-Fuentes; Craig B. Clements; Xindi Bian; Warren E. Heilman; Joseph J. Charney; Mario M. Valero; Adam K. Kochanski; Michael T. Kiefer (Agricultural and Forest Meteorology, 2024)

Geochemistry and mineralogy of muds and thermal waters from mud volcanoes in the NW Caribbean Coast of Colombia and their potential for pelotherapy - Maurizio Palmisano; Giuseppina Balassone; Sabino Maggi; Alexander Armesto Arenas; Iber M. Banda Guerra; Luis E. Correa Valero; Feliciano Ippolito; Nicola Mondillo; David F. Morales Giraldo; Angela Mormone; Annamaria Pellino; Francesco Putzolu; et al. (CATENA, 2024)

Correlation of hepatitis E and rat hepatitis E viruses urban wastewater monitoring and clinical cases - Maria Casares-Jimenez; Transito Garcia-Garcia; José M. Suárez-Cárdenas; Ana B. Perez-Jimenez; María A. Martín; Javier Caballero-Gómez; Carmen Michán; Diana Corona-Mata; María A. Risalde; Ignacio Perez-Valero; Rafael Guerra; Ignacio Garcia-Bocanegra; et al. (Science of The Total Environment, 2024)

Expert-driven play Fairway Analysis applied to the Azufral Volcano Geothermal Area in southwestern Colombia - Emmanuel Olvera-García; Bridget F. Ayling; Jesús B. Rueda-Gutiérrez; Anieri M. Morales Rivera; Gilbert F. Rodríguez-Rodríguez; Jaison Malo; Jefferson Sánchez; Yeimy Rodríguez-Molina; Yerson Pardo; Yenny P. Casallas-Veloza; J. Camilo Matiz-León; Gina Rodríguez-Ospina; et al. (Geothermics, 2023)

Assessing Listeria monocytogenes growth kinetics in rice pudding at different storage temperatures - Abdelraheem Hussein; Arícia Possas; Alshimaa A. Hassanien; Eman M. Shaker; Antonio Valero (International Journal of Food Microbiology, 2023)

A new iodometric microwave-assisted method for peroxide determination in Secondary Organic Aerosols - D. Alba-Elena; M.T. Baeza-Romero; M. Antiñolo; Eva María Espildora-García; Edelmira Valero (Atmospheric Environment, 2023)

Embryonic Development of Pediculus humanus capitis: Morphological Update and Proposal of New External Markers for the Differentiation Between Early, Medium, and Late Eggs - Blanca E. Álvarez-Fernández; M. Adela Valero; Benjamín Nogueda-Torres; M. María Morales-Suárez-Varela (Acta Parasitologica, 2023)
Background and Objectives The head louse Pediculus humanus capitis is a cosmopolitan ectoparasite that causes pediculosis. In the study of human lice, little research focuses on embryonic development. Currently, external markers of embryonic development represent a new approach in the evaluation of ovicidal drugs. The objective of this work was to update the morphology of embryonic development and propose novel external markers to differentiate between early, medium, or late P. h. capitis eggs. Methods Using stereoscopic light microscopy, we describe the morphological characteristics of P. h. capitis eggs with a special focus on embryonic development. Results The morphological analysis of the eggs revealed the presence of an operculum with ten aeropyles, although no micropyles were observed. For the first time, the presence of defective eggs that were non-viable due to the apparent absence of yolk granules was documented. The early eggs presented yolk granules and developing germ bands, while the medium eggs presented an embryonic rudiment and the outlines of the eyes and limbs. In late eggs, the head with eyes and antennae, the thorax with three pairs of legs, and the abdomen with six pairs of spiracles were observed as formed structures. At the end of this stage, the embryos acquired the morphology of the nymph I stage. Conclusion We propose novel biomarkers (e.g., the presence of spiracles and antennae, the proportion of the egg occupied by the embryo) to facilitate the differentiation between the developmental stages. The updated morphological characteristics of P. h. capitis eggs facilitate the standardization of toxicological tests in the quest for ovicidal drugs.

Antidiabetic and anti-obesity properties of a polyphenol-rich flower extract from Tagetes erecta L. and its effects on Caenorhabditis elegans fat storages - Sonia Núñez; Cristina Moliner; Marta Sofía Valero; Ahmed M. Mustafa; Filippo Maggi; Carlota Gómez-Rincón; Víctor López (Journal of Physiology and Biochemistry, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by a high blood sugar level that can cause severe complications to the organism or even death when not treated. However, certain dietary habits and foods may have beneficial effects on this condition. A polyphenolic-rich extract (containing hyperoside, isoquercitrin, quercetin, ellagic acid, and vanillic acid) of Tageres erecta L. ( T. erecta ) was obtained from yellow and orange flowers using an ethanolic Soxhlet extraction. These extracts were screened for antidiabetic and anti-obesity properties using in vitro and in vivo procedures. The capacity to inhibit the enzymes lipase and α-glucosidase, as well as the inhibition of advance glycation end-products (AGEs) was tested in vitro. Caenorhabditis elegans (C. elegans) was used as an obesity in vivo model to assess extracts effects on fat accumulation using the wild-type strain N2 and a mutant with no N3 fatty acid desaturase activity BX24. Extracts from both cultivars (yellow and orange) T. erecta presented in vitro inhibitory activity against the enzymes lipase and α-glucosidase, showing lower IC 50 values than acarbose (control). They also showed important activity in preventing AGEs formation. The polyphenol-rich matrices reduced the fat content of obese worms in the wild-type strain (N2) down to levels of untreated C. elegans , with no significant differences found between negative control (100% reduction) and both tested samples ( p < 0.05). Meanwhile, the fat reduction was considerably lower in the BX24 mutants (fat-1(wa-9)), suggesting that N3 fatty acid desaturase activity could be partially involved in the T. erecta flower effect. Our findings suggested that polyphenols from T. erecta can be considered candidate bioactive compounds in the prevention and improvement of metabolic chronic diseases such as obesity and diabetes.

Water, environment, and socioeconomic justice in California: A multi-benefit cropland repurposing framework - Angel Santiago Fernandez-Bou; José M. Rodríguez-Flores; Alexander Guzman; J. Pablo Ortiz-Partida; Leticia M. Classen-Rodriguez; Pedro A. Sánchez-Pérez; Jorge Valero-Fandiño; Chantelise Pells; Humberto Flores-Landeros; Samuel Sandoval-Solís; Gregory W. Characklis; Thomas C. Harmon; et al. (Science of The Total Environment, 2023)

Multidisciplinary assessment of the agricultural supply of desalinated seawater in south-eastern Spain - V. Martínez-Alvarez; A. Imbernón-Mulero; B. Gallego-Elvira; M. Soto-García; J.F. Maestre-Valero (Desalination, 2023)

Age-dependent association of clonal hematopoiesis with COVID-19 mortality in patients over 60 years - Marta Del Pozo-Valero; Marta Corton; Rosario López-Rodríguez; Ignacio Mahillo-Fernández; Javier Ruiz-Hornillos; Pablo Minguez; Cristina Villaverde; María Elena Pérez-Tomás; María Barreda-Sánchez; Esther Mancebo; Lidia Fernández-Caballero; Ruth Fernández Sanchez; et al. (GeroScience, 2023)
Clonal hematopoiesis, especially that of indeterminate potential (CHIP), has been associated with age-related diseases, such as those contributing to a more severe COVID-19. Four studies have attempted to associate CHIP with COVID-19 severity without conclusive findings. In the present work, we explore the association between CHIP and COVID-19 mortality. Genomic DNA extracted from peripheral blood of COVID-19 patients ( n = 241 deceased, n = 239 survivors) was sequenced with the Myeloid Solutions™ panel of SOPHiA Genetics. The association between clonality and age and clonality and mortality was studied using logistic regression models adjusted for sex, ethnicity, and comorbidities. The association with mortality was performed with patients stratified into four groups of age according to the quartiles of the distribution: 60–74 years, 75–84 years, 85–91 years, and 92–101 years. Clonality was found in 38% of the cohort. The presence of CHIP variants, but not the number, significantly increased with age in the entire cohort of COVID-19 patients, as well as in the group of survivors ( p < 0.001). When patients were stratified by age and the analysis adjusted, CHIP classified as pathogenic/likely pathogenic was significantly more represented in deceased patients compared with survivors in the group of 75–84 years (34.6% vs 13.7%, p = 0.020). We confirmed the well-established linear relationship between age and clonality in the cohort of COVID-19 patients and found a significant association between pathogenic/likely pathogenic CHIP and mortality in patients from 75 to 84 years that needs to be further validated.

Correction: The two-spotted leafhopper, Sophonia orientalis, (Hemiptera: Cicadellidae): a new threat to European vineyards - Dora Aguin-Pombo; António M. F. Aguiar; Délia Cravo; Adrià Miralles-Nuñez; Noemí Luque-Arnau; Pablo Valero; Jordi Sabaté (Applied Entomology and Zoology, 2023)

The two-spotted leafhopper, Sophonia orientalis, (Hemiptera: Cicadellidae): a new threat to European vineyards - Dora Aguin-Pombo; António M. F. Aguiar; Délia Cravo; Adrià Miralles-Nuñez; Noemí Luque-Arnau; Pablo Valero; Jordi Sabaté (Applied Entomology and Zoology, 2023)

Global Sensitivity Analysis of a Coupled Hydro-Economic Model and Groundwater Restriction Assessment - José M. Rodríguez-Flores; Jorge A. Valero Fandiño; Spencer A. Cole; Keyvan Malek; Tina Karimi; Harrison B. Zeff; Patrick M. Reed; Alvar Escriva-Bou; Josué Medellín-Azuara (Water Resources Management, 2022)
Assessing impacts on coupled food-water systems that may emerge from water policies, changes in economic drivers and crop productivity requires an understanding of dominant uncertainties. This paper assesses how a candidate groundwater pumping restriction and crop prices, crop yields, surface water price, electricity price, and parametric uncertainties shape economic and groundwater performance metrics from a coupled hydro-economic model (HEM) through a diagnostic global sensitivity analysis (GSA). The HEM used in this study integrates a groundwater depth response, modeled by an Artificial Neural Network (ANN), into a calibrated Positive Mathematical Programming (PMP) agricultural production model. Results show that in addition to a groundwater pumping restriction, performance metrics are highly sensitive to prices and yields of perennial tree crops. These sensitivities become salient during dry years when there is a higher reliance on groundwater. Furthermore, results indicate that performing a GSA for two different water baseline conditions used to calibrate the production model, dry and wet, result in different sensitivity indices magnitudes and factor prioritization. Diagnostic GSA results are used to understand key factors that affect the performance of a groundwater pumping restriction policy. This research is applied to the Wheeler Ridge-Maricopa Water Storage District located in Kern County, California, region reliant on groundwater and vulnerable to surface water shortages.

Sex and gametogenesis stage are strong drivers of gene expression in Mytilus edulis exposed to environmentally relevant plasticiser levels and pH 7.7 - Luana Fiorella Mincarelli; Emma C. Chapman; Jeanette M. Rotchell; Alexander P. Turner; Katharina C. Wollenberg Valero (Environmental Science and Pollution Research, 2022)
Plastic pollution and changes in oceanic pH are both pressing environmental issues. Little emphasis, however, has been placed on the influence of sex and gametogenesis stage when investigating the effects of such stressors. Here, we examined histology and molecular biomarkers of blue mussels Mytilus edulis exposed for 7 days to a pH 7.7 scenario (− 0.4 units) in combination with environmentally relevant concentrations (0, 0.5 and 50 µg/L) of the endocrine disrupting plasticiser di-2-ethylhexyl phthalate (DEHP). Through a factorial design, we investigated the gametogenesis cycle and sex-related expression of genes involved in pH homeostasis, stress response and oestrogen receptor-like pathways after the exposure to the two environmental stressors. As expected, we found sex-related differences in the proportion of developing, mature and spawning gonads in histological sections. Male gonads also showed higher levels of the acid–base regulator CA2 , but females had a higher expression of stress response-related genes (i.e. sod , cat , hsp70 ). We found a significant effect of DEHP on stress response-related gene expression that was dependent on the gametogenesis stage, but there was only a trend towards downregulation of CA2 in response to pH 7.7. In addition, differences in gene expression between males and females were most pronounced in experimental conditions containing DEHP and/or acidified pH but never the control, indicating that it is important to consider sex and gametogenesis stage when studying the response of mussels to diverse stressors.

Wind kinetic energy climatology and effective resolution for the ERA5 reanalysis - P. Bolgiani; C. Calvo-Sancho; J. Díaz-Fernández; L. Quitián-Hernández; M. Sastre; D. Santos-Muñoz; J. I. Farrán; J. J. González-Alemán; F. Valero; M. L. Martín (Climate Dynamics, 2022)
ERA5 represents the state of the art for atmospheric reanalyses and is widely used in meteorological and climatological research. In this work, this dataset is evaluated using the wind kinetic energy spectrum. Seasonal climatologies are generated for 30° latitudinal bands in the Northern Hemisphere (periodic domain) and over the North Atlantic area (limited-area domain). The spectra are also assessed to determine the effective resolution of the reanalysis. The results present notable differences between the latitudinal domains, indicating that ERA5 is properly capturing the synoptic conditions. The seasonal variability is adequate too, being winter the most energetic, and summer the least energetic season. The limited area domain results introduce a larger energy density and range. Despite the good results for the synoptic scales, the reanalysis’ spectra are not able to properly reproduce the dissipation rates at mesoscale. This is a source of uncertainties which needs to be taken into account when using the dataset. Finally, a cyclone tropical transition is presented as a case study. The spectrum generated shows a clear difference in energy density at every wavelength, as expected for a highly-energetic status of the atmosphere.

Event selection for dynamical downscaling: a neural network approach for physically-constrained precipitation events - J. J. Gómez-Navarro; C. C. Raible; J. A. García-Valero; M. Messmer; J. P. Montávez; O. Martius (Climate Dynamics, 2022)

C-band synthetic aperture radar (SAR) imagery for the classification of diverse cropping systems - Laura Dingle Robertson; Andrew M. Davidson; Heather McNairn; Mehdi Hosseini; Scott Mitchell; Diego de Abelleyra; Santiago Verón; Guerric le Maire; Milena Plannells; Silvia Valero; Nima Ahmadian; Alisa Coffin; et al. (International Journal of Remote Sensing, 2020)

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

Petrological and geochemical variations of a turbidite-like metasedimentary sequence over the metatexite to diatexite transition within the Pampean Orogen, Argentina - Juan E. Otamendi; Matías G. Barzola; Alina M. Tibaldi; Eber A. Cristofolini; Antonio M. Álvarez-Valero; Alejandro H. Demichelis (International Journal of Earth Sciences, 2019)

Effect of freezing and storage temperature on stability and antimicrobial activity of an antibiotic mixture used for decontamination of tissue allografts - Vicente Mirabet; Ana Melero; M. Dolores Ocete; Dimitra Bompou; Miriam Torrecillas; Juan J. Carreras; Isabel Valero; Ana I. Marqués; Rafael Medina; Luis R. Larrea; Cristina Arbona; Teresa M. Garrigues; et al. (Cell and Tissue Banking, 2018)

The obligate alkalophilic soda‐lake fungus Sodiomyces alkalinus has shifted to a protein diet - Alexey A. Grum‐Grzhimaylo; Daniel L. Falkoski; Joost van den Heuvel; Claudio A. Valero‐Jiménez; Byoungnam Min; In‐Geol Choi; Anna Lipzen; Chris G. Daum; Duur K. Aanen; Adrian Tsang; Bernard Henrissat; Elena N. Bilanenko; et al. (Molecular Ecology, 2018)
Sodiomyces alkalinus is one of the very few alkalophilic fungi, adapted to grow optimally at high pH . It is widely distributed at the plant‐deprived edges of extremely alkaline lakes and locally abundant. We sequenced the genome of S. alkalinus and reconstructed evolution of catabolic enzymes, using a phylogenomic comparison. We found that the genome of S. alkalinus is larger, but its predicted proteome is smaller and heavily depleted of both plant‐degrading enzymes and proteinases, when compared to its closest plant‐pathogenic relatives. Interestingly, despite overall losses, S. alkalinus has retained many proteinases families and acquired bacterial cell wall‐degrading enzymes, some of them via horizontal gene transfer from bacteria. This fungus has very potent proteolytic activity at high pH values, but slowly induced low activity of cellulases and hemicellulases. Our experimental and in silico data suggest that plant biomass, a common food source for most fungi, is not a preferred substrate for S. alkalinus in its natural environment. We conclude that the fungus has abandoned the ancestral plant‐based diet and has become specialized in a more protein‐rich food, abundantly available in soda lakes in the form of prokaryotes and small crustaceans.

Extreme maximum temperature events and their relationships with large-scale modes: potential hazard on the Iberian Peninsula - Andrés Merino; M. L. Martín; S. Fernández-González; J. L. Sánchez; F. Valero (Theoretical and Applied Climatology, 2018)

Diabetes modifies the role of prostanoids and potassium channels which regulate the hypereactivity of the rabbit renal artery to BNP - José M. Centeno; Luis Miranda-Gómez; Mikahela A. López-Morales; Teresa Jover-Mengual; María C. Burguete; Vannina G. Marrachelli; María Castelló-Ruiz; Alicia Aliena-Valero; Enrique Alborch; Francisco J. Miranda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Last deglaciation and Holocene environmental change at high altitude in the Pyrenees: the geochemical and paleomagnetic record from Marboré Lake (N Spain) - B. Oliva-Urcia; A. Moreno; M. Leunda; B. Valero-Garcés; P. González-Sampériz; G. Gil-Romera; M. P. Mata (Journal of Paleolimnology, 2018)

Historic hydrovolcanism at Deception Island (Antarctica): implications for eruption hazards - Dario Pedrazzi; Károly Németh; Adelina Geyer; Antonio M. Álvarez-Valero; Gerardo Aguirre-Díaz; Stefania Bartolini (Bulletin of Volcanology, 2018)

Evapotranspiration and carbon exchange in a citrus orchard using eddy covariance - J. F. Maestre-Valero; L. Testi; M. A. Jiménez-Bello; J. R. Castel; D. S. Intrigliolo (Irrigation Science, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Entangled fates of holobiont genomes during invasion: nested bacterial and host diversities in Caulerpa taxifolia - S. Arnaud‐Haond; T. Aires; R. Candeias; S. J. L. Teixeira; C. M. Duarte; M. Valero; E. A. Serrão (Molecular Ecology, 2017)
Successful prevention and mitigation of biological invasions requires retracing the initial steps of introduction, as well as understanding key elements enhancing the adaptability of invasive species. We studied the genetic diversity of the green alga Caulerpa taxifolia and its associated bacterial communities in several areas around the world. The striking congruence of α and β diversity of the algal genome and endophytic communities reveals a tight association, supporting the holobiont concept as best describing the unit of spreading and invasion. Both genomic compartments support the hypotheses of a unique accidental introduction in the Mediterranean and of multiple invasion events in southern Australia. In addition to helping with tracing the origin of invasion, bacterial communities exhibit metabolic functions that can potentially enhance adaptability and competitiveness of the consortium they form with their host. We thus hypothesize that low genetic diversities of both host and symbiont communities may contribute to the recent regression in the Mediterranean, in contrast with the persistence of highly diverse assemblages in southern Australia. This study supports the importance of scaling up from the host to the holobiont for a comprehensive understanding of invasions.

Natural products from Peperomia: occurrence, biogenesis and bioactivity - Yasmin Valero Gutierrez; Lydia F. Yamaguchi; Marcilio M. de Moraes; Christopher S. Jeffrey; Massuo J. Kato (Phytochemistry Reviews, 2016)

Angiotensin AT2-receptor stimulation improves survival and neurological outcome after experimental stroke in mice - Katja Schwengel; Pawel Namsolleck; Kristin Lucht; Bettina H. Clausen; Kate L. Lambertsen; Veronica Valero-Esquitino; Christa Thöne-Reineke; Susanne Müller; Robert E. Widdop; Kate M. Denton; Masatsugu Horiuchi; Masaru Iwai; et al. (Journal of Molecular Medicine, 2016)

Status, trends and drivers of kelp forests in Europe: an expert assessment - R. M. Araújo; J. Assis; R. Aguillar; L. Airoldi; I. Bárbara; I. Bartsch; T. Bekkby; H. Christie; D. Davoult; S. Derrien-Courtel; C. Fernandez; S. Fredriksen; et al. (Biodiversity and Conservation, 2016)

QR Codes: Outlook for Food Science and Nutrition - Javier Sanz-Valero; Luis M Álvarez Sabucedo; Carmina Wanden-Berghe; Juan M Santos Gago (Critical Reviews in Food Science and Nutrition, 2016)

Epidemiological risk factors associated with inflammatory breast cancer subtypes - Rachel L. Atkinson; Randa El-Zein; Vicente Valero; Anthony Lucci; Therese B. Bevers; Tamer Fouad; Weiqin Liao; Naoto T. Ueno; Wendy A. Woodward; Abenaa M. Brewster (Cancer Causes & Control, 2016)

A partial study of vertical distribution of conventional no-till seeders and spatial variability of seed depth placement of maize in the Alentejo region, Portugal - L. A. Conceição; P. Barreiro; S. Dias; M. Garrido; C. Valero; J. R. Marques da Silva (Precision Agriculture, 2016)

Western Mediterranean climate and environment since Marine Isotope Stage 3: a 50,000-year record from Lake Banyoles, Spain - Jack H. Lacey; Melanie J. Leng; Nicole Höbig; Jane M. Reed; Blas Valero-Garcés; Klaus Reicherter (Journal of Paleolimnology, 2016)

Development and characterization of microsatellite markers in two agarophyte species, Gracilaria birdiae and Gracilaria caudata (Gracilariaceae, Rhodophyta), using next-generation sequencing - L. M. Ayres-Ostrock; S. Mauger; E. M. Plastino; M. C. Oliveira; M. Valero; C. Destombe (Journal of Applied Phycology, 2016)

Bioaccumulation of pathogenic bacteria and amoeba by zebra mussels and their presence in watercourses - R. Mosteo; P. Goñi; N. Miguel; J. Abadías; P. Valero; M. P. Ormad (Environmental Science and Pollution Research, 2016)

CIAS detection of Fasciola hepatica/F. gigantica intermediate forms in bovines from Bangladesh - Syed Ali Ahasan; M. Adela Valero; Emdadul Haque Chowdhury; Mohammad Taohidul Islam; Mohammad Rafiqul Islam; Mohammad Motahar Hussain Mondal; Raquel V. Peixoto; Lavinia Berinde; Miroslava Panova; Santiago Mas-Coma (Acta Parasitologica, 2016)
Fascioliasis is an important food-borne parasitic zoonosis caused by two trematode species,

Sensitivity of two Iberian lakes to North Atlantic atmospheric circulation modes - Armand Hernández; Ricardo M. Trigo; Sergi Pla-Rabes; Blas L. Valero-Garcés; Sonia Jerez; Mayte Rico-Herrero; José C. Vega; Margarita Jambrina-Enríquez; Santiago Giralt (Climate Dynamics, 2015)

Temporal variation of PM10 and metal concentrations in Tampico, Mexico - R. M. Flores-Rangel; P. F. Rodríguez-Espinosa; J. A. Montes de Oca-Valero; V. Mugica-Álvarez; M. E. Ortiz-Romero-Vargas; M. Navarrete-López; H. J. Dorantes-Rosales; S. S. Morales-García (Air Quality, Atmosphere & Health, 2015)

Linking coastal aquaculture of meagre Argyrosomus regius and Western Mediterranean coastal fisheries through escapes incidents - P. Arechavala‐Lopez; J. M. Valero‐Rodriguez; J. Peñalver‐García; D. Izquierdo‐Gomez; P. Sanchez‐Jerez (Fisheries Management and Ecology, 2015)
Escape incidents in coastal aquaculture lead to economic losses for farmers and may have indirect socio‐economic effects on local fisheries. In this study, the relationship of meagre, Argyrosomus regius (Asso), production in open‐sea cages and coastal small‐scale fisheries was analysed through captures of escapes, which are easily detected because this species is considered locally absent in native communities in Western Mediterranean regions. Scale reading showed that 100% of captured meagre were escapees. The existence of a direct relationship, in terms of biomass, between the development of meagre coastal aquaculture and the increase of captures of this species by local fisheries was demonstrated. The spatial distribution of meagre captures suggested that there is a local environmental and economic interaction between meagre aquaculture and fisheries through escapees. Monitoring the presence of locally absent species such as meagre within landings might help to assess the magnitude of escapes, the potential economic effects on local aquaculture and fishery industries, and the potential adverse ecological impacts on local ecosystems.

Challenges in the Modeling of Wound Healing Mechanisms in Soft Biological Tissues - C. Valero; E. Javierre; J. M. García-Aznar; A. Menzel; M. J. Gómez-Benito (Annals of Biomedical Engineering, 2015)

The effects of the NAO on the ice phenology of Spanish alpine lakes - G. Sánchez-López; A. Hernández; S. Pla-Rabes; M. Toro; I. Granados; J. Sigró; R. M. Trigo; M. J. Rubio-Inglés; L. Camarero; B. Valero-Garcés; S. Giralt (Climatic Change, 2015)

Liver fluke (Fasciola hepatica) naturally infecting introduced European brown hare (Lepus europaeus) in northern Patagonia: phenotype, prevalence and potential risk - Pablo F. Cuervo; Sophia Di Cataldo; M. Cecilia Fantozzi; Erika Deis; Gabriela Diaz Isenrath; Gabriela Viberti; Patricio Artigas; Raquel Peixoto; M. Adela Valero; Roberto Mera y Sierra; Santiago Mas-Coma (Acta Parasitologica, 2015)
Fascioliasis has recently been included in the WHO list of Neglected Zoonotic Diseases. Besides being a major veterinary health problem, fascioliasis has large underdeveloping effects on the human communities affected. Though scarcely considered in fascioliasis epidemiology, it is well recognized that both native and introduced wildlife species may play a significant role as reservoirs of the disease. The objectives are to study the morphological characteristics of Fasciola hepatica adults and eggs in a population of Lepus europaeus, to assess liver fluke prevalence, and to analyze the potential reservoir role of the European brown hare in northern Patagonia, Argentina, where fascioliasis is endemic. Measures of F. hepatica found in L. europaeus from northern Patagonia demonstrate that the liver fluke is able to fully develop in wild hares and to shed normal eggs through their faeces. Egg shedding to the environment is close to the lower limit obtained for pigs, a domestic animal whose epidemiological importance in endemic areas has already been highlighted. The former, combined with the high prevalence found (14.28%), suggest an even more important role in the transmission cycle than previously considered. The results obtained do not only remark the extraordinary plasticity and adaptability of this trematode species to different host species, but also highlight the role of the European brown hare, and other NIS, as reservoirs capable for parasite spillback to domestic and native cycle, representing a potentially important, but hitherto neglected, cause of disease emergence.

Cavity types and microclimate: implications for ecological, evolutionary, and conservation studies - M. Amat-Valero; M. A. Calero-Torralbo; R. Václav; F. Valera (International Journal of Biometeorology, 2014)

Quantification of the Transcripts Encoding Different Forms of AChE in Various Cell Types: Real-Time PCR Coupled with Standards in Revealing the Copy Number - Cathy W.C. Bi; Wilson K.W. Luk; María-Letizia Campanari; Yuen H. Liu; Li Xu; Kei M. Lau; Miranda L. Xu; Roy C.Y. Choi; Javier Sáez-Valero; Karl W.K. Tsim (Journal of Molecular Neuroscience, 2014)

Spatiotemporal changes in the genetic diversity of harmful algal blooms caused by the toxic dinoflagellate A lexandrium minutum - A. Dia; L. Guillou; S. Mauger; E. Bigeard; D. Marie; M. Valero; C. Destombe (Molecular Ecology, 2014)
Organisms with sexual and asexual reproductive systems benefit from both types of reproduction. Sexual recombination generates new combinations of alleles, whereas clonality favours the spread of the fittest genotype through the entire population. Therefore, the rate of sexual vs. clonal reproduction has a major influence on the demography and genetic structure of natural populations. We addressed the effect of reproductive system on populations of the dinoflagellate Alexandrium minutum . More specifically, we monitored the spatiotemporal genetic diversity during and between bloom events in two estuaries separated by 150 km for two consecutive years. An analysis of population genetic patterns using microsatellite markers revealed surprisingly high genotypic and genetic diversity. Moreover, there was significant spatial and temporal genetic differentiation during and between bloom events. Our results demonstrate that (i) interannual genetic differentiation can be very high, (ii) estuaries are partially isolated during bloom events and (iii) genetic diversity can change rapidly during a bloom event. This rapid genetic change may reflect selective effects that are nevertheless not strong enough to reduce allelic diversity. Thus, sexual reproduction and/or migration may regularly erase any genetic structure produced within estuaries during a bloom event.

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Intergametophytic selfing and microgeographic genetic structure shape populations of the intertidal red seaweed C hondrus crispus - S. A. Krueger‐Hadfield; D. Roze; S. Mauger; M. Valero (Molecular Ecology, 2013)
Understanding how abiotic factors influence the spatial distribution of genetic variation provides insight into microevolutionary processes. The intertidal seascape is characterized by highly heterogeneous habitats which probably influence the partitioning of genetic variation at very small scales. The effects of tidal height on genetic variation in both the haploid (gametophytes) and diploid (tetrasporophytes) stages of the red alga C hondrus crispus were studied. Fronds were sampled every 25 cm within a 5 m × 5 m grid and along a 90‐m transect at two shore heights (high and low) in one intertidal site in F rance. The multilocus genotype of 799 fronds was determined ( N haploid = 586; N diploid = 213) using eight microsatellite loci to test the following hypotheses: (i) high and low shore fronds belong to genetically differentiated populations, (ii) gene flow is restricted within the high shore habitat due to tidal‐influenced isolation and (iii) significant F IS values are driven by life history characteristics. Pairwise F ST estimates between high and low shore levels supported the hypothesis that high and low shore fronds were genetically differentiated. The high shore was characterized by the occurrence of within‐shore genetic differentiation, reduced genetic diversity and increased levels of intergametophytic selfing, suggesting it is a marginal environment. These results suggest at fine scales within the intertidal seascape the same mechanisms as those over the species’ distributional range are at work with core and marginal population dynamics.

Lignin analysis using microwave digestion - Fatma Gassara; C. M. Ajila; Satinder K. Brar; R. D. Tyagi; M. Verma; J. R. Valero (Biotechnology Letters, 2012)

The Effects of Hydraulic and Organic Loadings on the Performance of a Full-Scale Facultative Pond in a Temperate Climate Region (Argentine Patagonia) - M. Faleschini; J. L. Esteves; M. A. Camargo Valero (Water, Air, & Soil Pollution, 2012)

Quantitative climate reconstruction linking meteorological, limnological and XRF core scanner datasets: the Lake Sanabria case study, NW Spain - S. Giralt; M. T. Rico-Herrero; J. C. Vega; B. L. Valero-Garcés (Journal of Paleolimnology, 2011)

Geochemical processes in a Mediterranean Lake: a high-resolution study of the last 4,000 years in Zoñar Lake, southern Spain - Celia Martín-Puertas; Blas L. Valero-Garcés; M. Pilar Mata; Ana Moreno; Santiago Giralt; Francisca Martínez-Ruiz; Francisco Jiménez-Espejo (Journal of Paleolimnology, 2011)

Dinucleotide microsatellite markers in the genus Caulerpa - Elena Varela-Álvarez; Travis C. Glenn; Ester A. Serrão; Carlos M. Duarte; Beatriz Martínez-Daranas; Myriam Valero; Núria Marbá (Journal of Applied Phycology, 2011)

Springtime coupled modes of regional wind in the Iberian Peninsula and large‐scale variability patterns - M. L. Martín; F. Valero; A. Morata; M. Y. Luna; A. Pascual; D. Santos‐Muñoz (International Journal of Climatology, 2011)
This paper investigates the relationships between the Global Circulation Model (GCM)‐simulated 1000 hPa geopotential heights (taken from the ERA40 reanalysis) over the North Atlantic and the regional wind over the Iberian Peninsula for springtime (March to May). The main goal is to recognize the atmospheric circulation patterns linked to wind anomaly configurations. The method used for the downscaling is singular value decomposition (SVD). After applying a Monte Carlo approach to assess the statistical significance of the obtained modes, the SVD analysis highlighted that the covariability is dominated by three main large‐scale features of the atmospheric circulation over the North Atlantic: (1) a first mode that relates local wind to the Scandinavian pattern (SCAN), by which a blocking pattern is linked to below‐normal winds, (2) a second covariability mode associated with the North Atlantic Oscillation (NAO) pattern that correlates with wind over Iberia. An enhanced spring NAO pattern is related to positive (negative) wind correlations over the northern (southern) Iberia and (3) a third SVD mode that relates wind to the East Atlantic (EA) pattern promoting a dissimilar behaviour in the Iberian wind with positive (negative) wind correlations in the western (eastern) part of Iberia. To conclude, composite maps were built up to give an average circulation associated with coherent wind variability over Iberia. Copyright © 2010 Royal Meteorological Society

The last deglaciation in the Picos de Europa National Park (Cantabrian Mountains, northern Spain) - Ana Moreno; Blas L. Valero‐Garcés; Montserrat Jiménez‐Sánchez; María José Domínguez‐Cuesta; M. Pilar Mata; Ana Navas; Penélope González‐Sampériz; Heather Stoll; Pedro Farias; Mario Morellón; J. Pablo Corella; Mayte Rico (Journal of Quaternary Science, 2010)
A sedimentological and geochemical study of the Lago Enol sequence (Cantabrian Mountains, northern Spain), together with detailed geomorphological mapping, provides a first record of glacier evolution and climate change over the last 40 ka in the Picos de Europa National Park. The Enol glacier retreated from its maximum extent prior to 40 ka BP as demonstrated by the onset of proglacial lacustrine sedimentation in two glaciated depressions: the Comella hollow to the north (before 40 ka BP) and the Lago Enol (before 38 ka BP). These results support previous evidence that the maximum extent of southern European glaciers occurred earlier than in northern Europe. Alternation of homogeneous and laminated proglacial sediments during the glacier retreat illustrate a dynamic glacial evolution during the Marine Isotope Stage (MIS) 3 (40–26 ka BP). A slight warming is detected at 26 ka ago with the change from proglacial sediments (in a lake located in contact to the glacier) to glaciolacustrine sedimentation (in a non‐contact or distal lake). Finally, the onset of organic‐rich sediments took place at 18 ka ago. This last transition occurred in two phases, similarly to the North Atlantic Last Termination, suggesting a link between North Atlantic Deep Water formation oscillations and palaeohydrological variability in the Cantabrian Mountains. Copyright © 2009 John Wiley & Sons, Ltd.

Characterization of the autumn Iberian precipitation from long‐term datasets: comparison between observed and hindcasted data - F. Valero; M. L. Martín; M. G. Sotillo; A. Morata; M. Y. Luna (International Journal of Climatology, 2009)
The present paper is focused on the analysis of the characterization of the autumn precipitation regime over the Iberian Peninsula. To this aim, different long‐term, observed, hindcasted and reanalysed datasets are used to analyse the 41‐year (1961–2001) time period. A long‐term high‐resolution precipitation database, derived from more than 4000 in situ observational stations, is used to characterize the rainfall regime. This observational data, used as a reference, allows the verification of the realism of different existing long‐term hindcasted and reanalysed products. These verification and comparison exercises were carried out with the autumn monthly hindcasted data derived from the high‐resolution Mediterranean Hindcast of Dynamic Processes of the Ocean and Coastal Areas of Europe (HIPOCAS) database, as well as the NCEP and ERA global reanalysis data. The characterization of autumn Iberian rainfall is carried out, both in terms of spatial and time variability, by means of spatial distribution of different statistics and a principal component analysis (PCA), as well as through an analysis based on wavelet methodology. The statistical comparative analysis between the HIPOCAS and the observed precipitation data shows a noticeable agreement existing between both datasets, highlighting that the Mediterranean HIPOCAS hindcast database is a useful tool that is able to accurately reproduce and largely capture the main spatial and time features that regionally configure the Iberian rainfall regime along the studied 41‐year period. Moreover, it is verified that the hindcasted HIPOCAS data notably improves the characterization of the autumn Iberian precipitation provided by the aforementioned global reanalysis products, asserting that the HIPOCAS precipitation dataset can well be used in regional studies related to hydrometeorology, statistical downscaling and climate variability. Copyright © 2008 Royal Meteorological Society

Elevated levels of interleukin-2 receptor and intercellular adhesion molecule 1 in sera from a venezuelan cohort of patients with dengue - N. Valero; Y. Larreal; L. M. Espina; I. Reyes; M. Maldonado; J. Mosquera (Archives of Virology, 2008)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Association of the F352V variant of the Klotho gene with bone mineral density - José A. Riancho; Carmen Valero; José L. Hernández; Fernando Ortiz; Ana Zarrabeitia; María A. Alonso; Nicolás Peña; M. Asunción Pascual; Jesús González-Macías; María T. Zarrabeitia (Biogerontology, 2007)

L-Tryptophan administered orally at night modifies the melatonin plasma levels, phagocytosis and oxidative metabolism of ringdove (Streptopelia roseogrisea) heterophils - J. Cubero; V. Valero; D. Narciso; M. Rivero; J.M. Marchena; A.B. Rodríguez; C. Barriga (Molecular and Cellular Biochemistry, 2006)

Validation of a homogeneous 41-year (1961–2001) winter precipitation hindcasted dataset over the Iberian Peninsula: assessment of the regional improvement of global reanalysis - M. G. Sotillo; M. L. Martín; F. Valero; M. Y. Luna (Climate Dynamics, 2006)

Self-similarity patterns of precipitation in the Iberian Peninsula - A. Morata; M. L. Martín; M. Y. Luna; F. Valero (Theoretical and Applied Climatology, 2006)

A high-resolution 44-year atmospheric hindcast for the Mediterranean Basin: contribution to the regional improvement of global reanalysis - M. G. Sotillo; A. W. Ratsimandresy; J. C. Carretero; A. Bentamy; F. Valero; F. González-Rouco (Climate Dynamics, 2005)

Rational strategy for the production of new crude lipases from Candida rugosa - Pablo Domínguez de María; José M. Sánchez-Montero; Andrés R. Alcántara; Francisco Valero; José V. Sinisterra (Biotechnology Letters, 2005)

Visual feedback alters the variations in corticospinal excitability that arise from rhythmic movements of the opposite limb - R. G. Carson; T. N. Welsh; M- Pamblanco-Valero (Experimental Brain Research, 2005)

Coupled modes of large-scale climatic variables and regional precipitation in the western Mediterranean in autumn - F. Valero; M. Y. Luna; M. L. Martn; A. Morata; F. Gonzlez-Rouco (Climate Dynamics, 2004)

North Atlantic teleconnection patterns of low‐frequency variability and their links with springtime precipitation in the western Mediterranean - M. L. Martín; M. Y. Luna; A. Morata; F. Valero (International Journal of Climatology, 2004)
The relationship between springtime (March–May) precipitation in the western Mediterranean area and several North Atlantic teleconnection patterns of low‐frequency variability is analysed for the period 1948–89. Singular value decomposition analysis (SVDA) of the springtime monthly mean fields for the three paired combinations of 300 hPa geopotential height–precipitation, 300 hPa zonal wind–precipitation and 300 hPa meridional wind–precipitation has shown that their covariability is dominated by two main large‐scale atmospheric circulation patterns. In every SVD combination, the first mode relates precipitation anomalies to the east Atlantic jet pattern. Above‐normal rainfall anomalies are linked with a blocking pattern affecting Iberian weather. The second covariability mode for the three SVD As takes into account the response of the precipitation to the North Atlantic oscillation (NAO) pattern. An enhanced spring NAO pattern is related to positive (negative) precipitation anomalies over the southern (northern) western Mediterranean. Through these two modes, the North Atlantic large‐scale atmospheric dynamics explains about 50% of the total spring precipitation variability in the western Mediterranean area. A Monte Carlo approach has allowed setting the statistical significance of the modes obtained and to assess the effectiveness of the western Mediterranean precipitation response to the teleconnection patterns. Copyright © 2004 Royal Meteorological Society

Spatial and Seasonal Variations of Water Quality in a Mediterranean Catchment: The Llobregat River (NE Spain) - J.L. Fernández-Turiel; D. Gimeno; J.J. Rodriguez; M. Carnicero; F. Valero (Environmental Geochemistry and Health, 2003)

Asynchroneity of maximum glacier advances in the central Spanish Pyrenees - José M. García‐Ruiz; Blas L. Valero‐Garcés; Carlos Martí‐Bono; Penélope González‐Sampériz (Journal of Quaternary Science, 2003)
The deglaciation history of the Escarra and Lana Mayor glaciers (Upper Gállego valley, central Spanish Pyrenees) had been reconstructed on the basis of detailed geomorphological studies of glacier deposits, sedimentological and palynological analyses of glacial lake sediments and an accelerator mass spectrometry (AMS) 14 C chronology based on minimum ages from glacial lake deposits. The maximum extent of the Pyrenean glaciers during the last glaciation was before 30 000 yr BP and pre‐dated the maximum advances of the Scandinavian Ice Sheet and some Alpine glaciers. A later advance occurred during the coldest period (around 20 000 yr BP), synchronous with the maximum global ice extent, but in the Pyrenees it was less extensive than the previous one. Later, there were minor advances followed by a stage of debris‐covered glaciers and a phase of moraine formation near cirque backwalls. The deglaciation chronology of the Upper Gállego valley provides more examples of the general asynchroneity between mountain and continental glaciers. The asynchroneity of maximum advances may be explained by different regional responses to climatic forcing and by the southern latitude of the Pyrenees. Copyright © 2002 John Wiley & Sons, Ltd.

Polymerase chain reaction–single strand conformation polymorphism analyses of nuclear and chloroplast DNA provide evidence for recombination, multiple introductions and nascent speciation in the Caulerpa taxifolia complex - I. Meusnier; M. Valero; C. Destombe; C. Godé; E. Desmarais; F. Bonhomme; W. T. Stam; J. L. Olsen (Molecular Ecology, 2002)
Independent lines of evidence support an Australian origin for the Mediterranean populations of the tropical alga Caulerpa taxifolia . To complement previous biogeographical studies based on nuclear rDNA internal transcribed spacer (ITS), a new chloroplast marker was developed — the cp 16S rDNA intron‐2. Sequence variability for both nuclear and chloroplast markers were assessed in 110 individuals using single strand conformation polymorphism. Comparison of intrapopulation genetic diversity between invasive Mediterranean and ‘native’ Australian populations revealed the occurrence of two divergent and widespread clades. The first clade grouped nontropical invasive populations with inshore‐mainland populations from Australia, while the second clustered all offshore‐island populations studied so far. Despite our finding of nine distinct nuclear and five distinct chloroplast profiles, a single nucleocytoplasmic combination was characteristic of the invasive populations and sexual reproduction was found to be very rare. C. taxifolia is clearly a complex of genetically and ecologically differentiated sibling species or subspecies.

Methanol determination in Pichia pastoris cultures by flow injection analysis - C. Almuzara; O. Cos; M. Baeza; D. Gabriel; F. Valero (Biotechnology Letters, 2002)

Mycobacterium peregrinum Bacteremia in an Immunocompromised Patient with a Hickman Catheter - M. Rodríguez-Gancedo; T. Rodríguez-González; G. Yagüe; P. Valero-Guillén; M. Segovia-Hernández (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Comparison of the accumulation of astaxanthin in Haematococcus pluvialis and other green microalgae under N-starvation and high light conditions - M. Orosa; J.F. Valero; C. Herrero; J. Abalde (Biotechnology Letters, 2001)

Phylogenetic analyses of Caulerpa taxifolia (Chlorophyta) and of its associated bacterial microflora provide clues to the origin of the Mediterranean introduction - I. Meusnier; J. L. Olsen; W. T. Stam; C. Destombe; M. Valero (Molecular Ecology, 2001)
The accidental introduction of Caulerpa taxifolia into the Mediterranean is no longer under dispute. What has eluded researchers until now, is definitive evidence for the original, biogeographical source population. Here we present two independent lines of evidence that support an Australian origin for the Mediterranean populations of C. taxifolia . First, we reanalysed algal rDNA‐internal transcribed spacer (rDNA‐ITS) sequences, combining previously published sequences from different studies with 22 new sequences. The ITS sequence comparison showed that the Australian sample is the sister group of the Mediterranean–aquarium clade. Second, cloned bacterial 16S rDNA gene sequences were analysed from the associated microflora of C. taxifolia collected from Australia, Tahiti, the Philippines and the Mediterranean. Five bacterial lineages were identified, of which three were dominant. Alpha Proteobacteria were the most abundant and were found in all samples. In contrast, members of the beta Proteobacterial line and Cytophaga‐Flexibacter‐Bacteroides line (CFB) were mainly associated with Mediterranean and Australian samples. Frequency distributions of the five bacterial lineages were significantly different among biogeographical locations. Phylogenetic analyses of the 54 bacterial sequences derived from the four C. taxifolia individuals resulted in a well‐resolved tree with high bootstrap support. The topologies of the beta Proteobacteria and CFB mirror the geographical sources of their algal hosts. Bacterial–algal associations provide an identification tool that may have wide application for the detection of marine invasions.

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Identification of random amplified polymorphic DNA (RAPD) markers highly linked to sex determination in the red alga Gracilaria gracilis - E. A. Martinez; C. Destombe; M. C. Quillet; M. Valero (Molecular Ecology, 1999)
The random amplified polymorphic DNA (RAPD) technique was employed in the haplo‐diploid dioecious species Gracilaria gracilis to identify sex‐linked PCR markers. Sixty‐nine decamer oligonucleotide primers were tested on two bulks of DNA, one from five haploid males and the other from five haploid females. One of these primers (OPD13) generated a 430‐bp fragment specific to males and a 620‐bp fragment specific to females. The diploid individuals (tetrasporophytes) showed the co‐occurrence of these two fragments. In order to verify the linkage between the sexual phenotypes and these markers, a progeny array of 59 haploid individuals (male and female) born on a diploid individual was analysed, in all of which the two markers produced by the OPD13 primer segregated perfectly with sex.

Characterization of microsatellite markers in the red alga Gracilaria gracilis - H Luo; M Möorchen; C. R Engel; C Destombe; J. T Epplen; C Epplen; P Saumitou‐Laprade; M Valero (Molecular Ecology, 1999)

Isolation and characterization of microsatellite markers in the nuclear genome of the brown alga Laminaria digitata (Phaeophyceae) - C. BILLOT; S. ROUSVOAL; A. ESTOUP; J. T. EPPLEN; P. SAUMITOU‐LAPRADE; M. VALERO; B. KLOAREG (Molecular Ecology, 1998)

Short allele dominance as a source of heterozygote deficiency at microsatellite loci: experimental evidence at the dinucleotide locus Gv1CT in Gracilaria gracilis (Rhodophyta) - R. WATTIER; C. R. ENGEL; P. SAUMITOU‐LAPRADE; M. VALERO (Molecular Ecology, 1998)
In this study, we compared the genotypes obtained at a microsatellite locus using two methods of amplification and detection of variation in a set of individuals belonging to the red alga haplo‐diploid species, Gracilaria gracilis . The methods varied in their capacity to detect longer alleles in heterozygotes, resulting in an apparent heterozygote deficiency. We attributed this bias in favour of short alleles to competition leading to the preferential amplification of shorter alleles (short allele dominance). To test this hypothesis, we created artificial heterozygotes (mixtures of two haploid DNA samples) and showed that long alleles already less intense than short alleles, ‘suffer’ more from being in association.

Distribution of chloroplast DNA diversity within and among populations in gynodioecious Beta vulgaris ssp. maritima (Chenopodiaceae) - D. FORCIOLI; P. SAUMITOU‐LAPRADE; M. VALERO; P. VERNET; J. CUGUEN (Molecular Ecology, 1998)
With the recent technical advances in molecular biology, chloroplast DNA (cpDNA) has become a marker used for the study of cytoplasmic differentiation of natural populations of plants. As chloroplasts are maternally inherited in most plant species, the seed component of gene flow is thus made accessible. We present here a study of cpDNA polymorphism within the maritima subspecies of the gynodioecious Beta vulgaris in which we try to assess the impact of such a reproductive system on seed flow. One hundred and eighty‐eight wild beets were sampled from 20 hermaphroditic and 20 gynodioecious (i.e. containing both hermaphroditic and female plants) populations from the Atlantic coast of Europe. cpDNA variability in these populations was characterized with a rapid restriction fragment length polymorphism (RFLP) method. Eight cpDNA haplotypes were found. Strong differentiation among populations was observed ( F ST = 0.43) and was consistent with isolation by distance, although most of the cpDNA haplotypes were ubiquitous. Gynodioecy seems to affect the distribution of cpDNA diversity: gynodioecious populations of Beta vulgaris ssp. maritima contained a greater number of cpDNA types but were less differentiated among themselves than hermaphroditic ones.

Genetic structure of natural populations of Gelidium species: A re-evaluation of results - P. A. Sosa; M. Valero; F. Batista; M. A. Gonzalez-Pérez (Journal of Applied Phycology, 1998)

Zinc and copper concentrations in serum from Spanish women during pregnancy - F. Martín-Lagos; M. Navarro-Alarcón; C. Terrés-Martos; H. López-García de la Serrana; V. Pérez-Valero; M. C. López-Martínez (Biological Trace Element Research, 1998)

Identification of de novo deletions at the NF1 gene: no preferential paternal origin and phenotypic analysis of patients - M. Carmen Valero; Ignacio Pascual-Castroviejo; E. Velasco; Felipe Moreno; Concepción Hernández-Chico (Human Genetics, 1997)